2015
DOI: 10.1089/met.2014.0146
|View full text |Cite
|
Sign up to set email alerts
|

Waist-to-Height Ratio and Triglycerides/High-Density Lipoprotein Cholesterol Were the Optimal Predictors of Metabolic Syndrome in Uighur Men and Women in Xinjiang, China

Abstract: WHtR was the best predictor of metabolic syndrome in Uighur men, whereas TGs/HDL-C was the best predictor of metabolic syndrome in Uighur women in Xinjiang.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
24
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 34 publications
4
24
2
Order By: Relevance
“…and salts and less exercise. Besides, the prevalence of MetS in Caucasians was higher than that in Asia (19). These studies confirmed that ethnic and life styles could contribute to the differences of MetS prevalence.…”
Section: Discussionsupporting
confidence: 62%
“…and salts and less exercise. Besides, the prevalence of MetS in Caucasians was higher than that in Asia (19). These studies confirmed that ethnic and life styles could contribute to the differences of MetS prevalence.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, the cost and availability of diagnostic tests based on the MetS criteria have hindered the mass screening among high risk population, especially among underdeveloped areas and developing countries. Recently, several studies supported the use of waist-to-height ratio (WHtR) for the screening of MetS789, which is consistent with the notion that the metabolic complications of obesity could be more closely related to visceral adiposity than overall adiposity101112. This is particularly important in Chinese population, who, despite being generally less obese, are more prone to visceral fat accumulation and insulin resistance compared with western populations13.…”
mentioning
confidence: 58%
“…Several visceral adiposity indicators, such as LAP and VAI appeared to be better indices to predict presence of MetS, relative to WHtR, which has been widely recommended based on previous studies789. To the best of our knowledge, this is the first large-scale population-based study to directly compare the screening ability of visceral adiposity indicators (LAP and VAI) and anthropometric indices (WHtR and BAI) for the screening of MetS in a multi-ethnic population.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies showed that certain parameters can be used in screening of metabolic syndrome such as waist-to-height ratio [13], lipid accumulation product which is estimated from waist circumference and plasma triglyceride levels [14] and triglyceride/HDL-C ratio [15]. In females, especially if obese or overweight, age at menarche may be one of such parameters.…”
Section: Discussionmentioning
confidence: 99%